1979
DOI: 10.1203/00006450-197904000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Transient Partial hGH Deficiency in Prepubertal Children with Delay of Growth

Abstract: SummaryThe hGH response to an ornithin or an insulin test was measured in 105 children from 11-18 yr old with delay of growth more than 2 SD. Besides 74 subjects with normal values and 7 with complete lack of response, 24 subjects exhibited a,partial rise of GH. Most of the latter had decreasing growth rate and no sign of puberty. Out of 15 assessed for GH function after onset of puberty, 14 showed a normal response accompanying a markedly increased growth velocity. Four other subjects with partial response wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
7

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(45 citation statements)
references
References 2 publications
(2 reference statements)
3
35
0
7
Order By: Relevance
“…The parents of children with CDG frequently reported a later growth spurt or a late age at menarche in concordance with the literature [8,9,26]. In CDG, a transient reduction in the secretion of GH [27,28] and GH-releasing hormone [29] has been reported. However, in our study, IGF-1 levels were in the lower normal range at the time of presentation at our clinic.…”
Section: Discussionsupporting
confidence: 71%
“…The parents of children with CDG frequently reported a later growth spurt or a late age at menarche in concordance with the literature [8,9,26]. In CDG, a transient reduction in the secretion of GH [27,28] and GH-releasing hormone [29] has been reported. However, in our study, IGF-1 levels were in the lower normal range at the time of presentation at our clinic.…”
Section: Discussionsupporting
confidence: 71%
“…The negative correlation of basal fasting G H with age may be related to the previously reported prepubertal decrease in G H secretion in short children (21,22,45,46); although the peak G H responses did not show this correlation. The negative correlation of second-test peak G H levels with the degree of bone age delay may also be related to this factor.…”
Section: Discussionmentioning
confidence: 58%
“…Although GH testing performed in peripubertal children with growth retardation may give subnormal results, a number of studies conducted in previous decades showed that approximately half of the children who exhibited low GH secretion and were eventually treated by GH had a normal GH response to stimulation tests at reassessment following cessation of treatment. Moreover, untreated children showed an acceleration of growth, with an increase in both spontaneous and stimulated GH secretion as they progressed through puberty [4,5,6,7]. These findings indicated that subnormal GH secretion in the peripubertal period most likely stemmed from a lack of sex hormones rather than GH deficiency.…”
Section: Introductionmentioning
confidence: 81%